EXPLORING THE EFFECTS OF ASYNCHRONOUS LEARNING ON ACADEMIC ACHIEVEMENT AND STUDENT LEARNING INDEPENDENCE - Sunarno Sunarno; Ahmad Aziz Fanani; Fathi Hidayah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
This study aims to explore the effectiveness of asynchronous learning in improving students' independence and academic achievement. The focus of this research is to understand how the time flexibility provided by asynchronous learning methods can affect students' independence in managing their study time as well as its impact on academic achievement. The research method used is a case study with data analysis using the Miles and Huberman technique. Data were collected through in-depth interviews and direct observation of students engaged in asynchronous learning. The results showed that 75% of students experienced an improvement in learning time management, 70% showed an increase in self-discipline, and 68% became more active in looking for additional learning resources. These findings indicate that asynchronous learning not only increases learning independence but also has a positive impact on students' academic achievement. The implication of this study is the importance of educational institutions to consider the integration of asynchronous learning methods in the curriculum to support the development of students' independence and academic achievement more effectively.